DAKWAH ISLAM DAN INOVASI MEDIA: PELUANG DAN ANCAMAN MEDIA GLOBAL ATAS DAKWAH ISLAM - Fakhruroji, Moch. (Fakultas Dakwah IAIN Purwokerto, 2010)
The development of dakwah science is not as fast as the development of dakwah activities. In this globalsociety, dakwah activities can even be found in the world wide web. They transform greatly in public space as spiritualteachings and are actualized in various forms. These various forms of dakwah activities are supported by dakwah media. Indakwah science, media becomes a channel used by the agents of dakwah activities to deliver the messages